biota Identifikasi Biota-Biota yang Berasosiasi pada Area Transplantasi Karang 'Coral Garden Stock Center' di Pantai Malalayang Manado - Youdy Joseph Hendrik Gumolili (PolimdoSains, 2021)
This research was carrid out in the coral reef transplantation Coral Garden Stock Center area of Malalayang in July 31st 2020 by using visual cencus method on coral transplantation. the result of the research show that there were 27 species of the reef fish and 14 other types of biota iving in association in the coral transplanttion area. key words: coral reef transplantation